Perspectives of older people toward Thai high-speed rail promotion using the theory of planned behavior and the unified theory of acceptance and use of technology - Watcharamaisakul, Fareeda; Phojaem, Thanakorn; Sum, Sonita; Champahom, Thanapong; Jomnonkwao, Sajjakaj; Wisutwattanasak, Panuwat; Dangbut, Adisorn; Ratanavaraha, Vatanavongs (Frontiers in Built Environment, 2025)
Today, the population growth rate in Thailand is very slow. In particular, the number of older people in Thailand is notably increasing. Many members of this group are reluctant to accept or use new technology. The government is formulating a support plan for a high-speed rail (HSR) system to develop the public transportation system to support better livelihood and reduce traffic problems, which may affect the use intent of older people. The factors that influence HSR use will support social coherence and help older people to adapt to and cope with newly developed technology in the future. This study aims to develop a perspective model of the influence of HSR use among older people by applying the theory of planned behavior (TPB) combined with the unified theory of acceptance and use of technology (UTAUT). Data were collected through a questionnaire survey on 3,200 people older than 60 in four regions in Thailand. Analysis was conducted using the structural equation model. The result indicated that all factors of TPB and UTAUT significantly influenced the behavioral intention of older people to use HSR. The factor with the largest influence was the attitude toward technology use, followed by subjective norms and facilitating conditions. Moreover, performance and effort expectancies play statistically significant roles in the attitude toward technology use.